Rancang Bangun dan Analisis Otomatisasi Alat Pengisian dan Pemadatan Media Tanam Jamur Kapasitas 171 Baglog/Jam dengan Sistem Pneumatik - Akhmad Fakhrur Rozi; Friska Ayu Fitrianti Sugiono (Politeknik Negeri Semarang, 2023)
Mushroom growing media filler and compactor machine is a machine to print baglog as mushroom growing media. The problems that faced by mushrooms farmer is low productivity, with this tool farmers can increase the productivity of mushroom filling and compaction baglog because the filling and compacting process use a pneumatic system.The method to manufacture mushroom growing media filler and compactor machine are the initial observations of the Small and Medium Enterprises (UKM). The development of electoral observation is form alternative designs, design, manufacturing, assembly until the testing process and data retrieval. The results of design automation of filling and compaction of the mushroom growing media using pneumatic system has a production capacity of 171baglog/hour by using a working pressure of 6 bar.